2018
DOI: 10.1002/ajb2.1197
|View full text |Cite
|
Sign up to set email alerts
|

Long‐ and short‐term responses ofAsclepiasspecies differ in respect to fire, grazing, and nutrient addition

Abstract: Premise of the Study The tallgrass prairie ecosystem has experienced a dramatic reduction over the past 150 yr. This reduction has impacted the abundance of native grassland species, including milkweeds (Asclepias). Methods We used two long‐term (27 yr) data sets to examine how fire, grazing, and nutrient addition shape milkweed abundance in tallgrass prairie. We compared these results to those of a greenhouse experiment that varied nutrient levels in the absence of competition, herbivory, and mutualistic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Indirect impacts due to ways in which fire affects monarch host plants or nectar plants are more likely. The effects of fire on common milkweed (Asclepias syriaca) are unclear; Towne and Kemp (2008) reported that A. syriaca declined in frequency after summer fire, but a recent study in Kansas found that it increased after fire and decreased with grazing, while seven other species of milkweeds increased with grazing (Ricono et al, 2018). In the southern Great Plains, Asclepias viridis density and re-growth were significantly higher immediately after summer burns, leading to an increase in observed monarch eggs and larvae in burned areas (Baum and Sharber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect impacts due to ways in which fire affects monarch host plants or nectar plants are more likely. The effects of fire on common milkweed (Asclepias syriaca) are unclear; Towne and Kemp (2008) reported that A. syriaca declined in frequency after summer fire, but a recent study in Kansas found that it increased after fire and decreased with grazing, while seven other species of milkweeds increased with grazing (Ricono et al, 2018). In the southern Great Plains, Asclepias viridis density and re-growth were significantly higher immediately after summer burns, leading to an increase in observed monarch eggs and larvae in burned areas (Baum and Sharber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fire may improve habitat for monarch butterflies (Nymphalidae: Danaus plexippus) by increasing the density of firefollowing Asclepias host species (Baum & Sharber, 2012;Ricono et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, butterflies, even within families, are highly variable in host plant specificity (Dyer et al., 2007), and this will likely affect butterfly response to fire at the species level (Gaigher et al., 2019; Huntzinger, 2003). For example, fire may improve habitat for monarch butterflies (Nymphalidae: Danaus plexippus ) by increasing the density of fire‐following Asclepias host species (Baum & Sharber, 2012; Ricono et al., 2018).…”
Section: Discussionmentioning
confidence: 99%